Eugenia Lincoln and the Unexpected Package - DiCamillo, Kate; Van Dusen, Chris (Somerville, Massachusetts : Candlewick Press, 2017)
When an unexpected package containing an accordion arrives, Eugenia Lincoln tries to get rid of the instrument by selling it, destroying it, and giving it away, but nothing works.
Keywords: Accordion -- Juvenile fiction; Surprise -- Juvenile fiction; Accordion -- Fiction; Surprise -- Fiction